(untitled) (Bangladesh Journal of Plant Breeding and Genetics, 2008)
Haymans analysis of variance (ANOVA) indicated importance of both additive and non-additive genetic components for all the grain characters. The ANOVA showed unidirectional dominance for the characters viz. kernel breadth, upper empty glume length and endosperm-embryo ratio, asymmetrical gene distribution for the characters viz. grain length, grain breadth, kernel length, kernel breadth and kernel thickness and residual dominance effects for all the grain characters studied. Five out of nine grain characters viz. grain breadth, grain thickness, kernel breadth, kernel thickness and upper empty glume length followed the simple additive-dominance genetic model. The rest of the grain characters showed nonallelic gene interaction or epistasis. According to Vr-Wr graph, partial dominance was involved in the action of genes governing the inheritance of grain breadth, grain thickness, kernel breadth and kernel thickness while complete dominance was involved in the inheritance of upper empty glume length. BR4828-54-4-1-4-9 contained the most of the recessive genes for four characters except upper empty glume length while Amol3 appeared to possess most of the recessive genes. On the other hand, Minikit for grain breadth, Amol3 for grain thickness and BRRI dhan29 for kernel breadth, kernel thickness and upper empty glume length possessed most of the dominant genes for the respective characters. The components of variance demonstrated involvement of both additive and dominant components in the inheritance of grain breadth, grain thickness, kernel breadth, kernel thickness and endosperm-embryo ratio. The distribution of dominant and recessive genes was unequal in the parents for grain breadth, kernel breadth, grain thickness, kernel thickness and upper empty glume length. Again, net dominance effects were in the negative direction for all the grain characters. There was drastic influence of environment on all the five grain characters following simple additive-dominance genetic model. Heritability in narrow sense (h2 n) was very high for grain breadth, grain thickness, kernel breadth and kernel thickness. However, h2 n for upper empty glume length was moderate. DOI: http://dx.doi.org/10.3329/bjpbg.v21i1.17047